Characterization of Injury Incurred by Escherichia coli upon Freeze-Drying - Sinskey, T. J. (1970)
When cells of Escherichia coli ML30 were suspended in 2% gelatin and frozen at −40 C, no appreciable metabolic damage or death occurred. After freeze-drying for 8 hr at a platen temperature of 49 C and rehydration with a mineral salts medium, survival of the cells was 0.6%. Metabolic damage of the survivors was found to be 23%. Permeability alterations were detected by several criteria. Freeze-dried cells were susceptible to antibiotics normally ineffective against E. coli and leakage of ribonucleic acid (RNA) occurred. Analysis of ribosomal extracts of rehydrated freeze-dried cells demonstrated the presence of appreciable degradation products. Permeability alterations were shown to be reversible by the observation that antibiotic susceptibility was a time-dependent process and that the gratuitous inducer of β-galactosidase was not concentrated by freeze-dried cells until the injured cells had been incubated in a nutrient medium for 300 min or more. At approximately the same time, metabolic damage was repaired. RNA synthesis preceded protein synthesis by about 150 min, and deoxyribonucleic acid synthesis occurred with the resumption of normal growth. This was interpreted to be the result of repair of RNA taking place before protein synthesis and growth could resume. A pronounced increase in the lag time of freeze-dried cells was also observed. Peptides and Casamino Acids shortened the lag time for freeze-dried cells but not for the controls. Glycerol and glucose were found to be better carbon sources for growth of freeze-dried cells than sodium lactate or sodium succinate.